Gaya Kepemimpinan Kepala Sekolah, Motivasi Kinerja Guru - Nurussalami Nurussalami (Bunayya, 2018)
Teacher performance can be influenced by some by several factors such as principal leadership style and teacher work motivation. Efforts to improve the performance of teachers, principals as leaders have duties and responsibilities and also play a role in motivating teachers and showing exemplary leadership. The purpose of this study is to know the description and performance of the principal: (1) the style of leadership of the principal to the performance of teachers of SD Negeri Siem Darussalam Aceh Besar subdistrict (2) work motivation on the performance of the teachers of SD Negeri Siem Kecamatan Darussalam; (3) principal leadership style and work motivation on teacher performance of SD Negeri Siem Darussalam Sub-district, Aceh Besar. The results of the study found that (1) the principal's leadership style on teacher performance showed a strong level so as to improve teacher performance. (2) teacher performance motivation in teacher self and given by principal shows enough level for teacher performance. (3) principal leadership style and work motivation together are positively and significantly correlated with teacher performance. The research method used is descriptive method with qualitative approach. The results of the study found that (1) the principal leadership style is very good on teacher performance (2) motivation on teacher performance (3) principal leadership style and work motivation together. The research method used is descriptive method with qualitative approach. The results of the study found that (1) the leadership style of the principal is very good on teacher performance, the leadership applied by the principal has shown a strong level so as to improve the teacher's performance (2) the motivation to the teacher's performance is in the teacher as well as given by the principal shows sufficient levels for teacher performance (3) leadership style of headmaster in motivating teacher work.